Discourse Interpretation of Public Policy in the Context of Enforcement of Foreign Arbitral Awards in Indonesia - Saraswati, AAA Nanda; Hidayat, Choirul (Brawijaya Law Journal, 2019)
The use of the concept of "public policy" by the national judiciary as a basis for the refusal of recognition and enforcement of foreign arbitral awards leaves an issue in the Indonesian judicial system. The main problem often questioned by the international community is that Indonesia refuses to enforce and even reject foreign arbitral awards on the grounds of violating public policy. This paper aims to analyze the interpretation of the concept of public policy used by judges as one of the reasons for the refusal of the recognition and enforcement of foreign arbitral awards and whether such interpretation is in accordance with international standards. The results shows that Indonesian courts tend to use a "domestic" approach when interpreting public policy namely as a provision and principles of law and national interests, rather than the international standard approach. Such approach have raised a number of critics from other countries. Not only because it is not in accordance with the values and principles of international law, but the interpretation is considered not to prioritize the purpose of the New York Convention, namely facilitating the recognition and enforcement of foreign arbitral awards